2016
DOI: 10.1137/151004896
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Reduction for a Class of Multiscale Fast-Slow Stochastic Dynamical Systems

Abstract: Multiple time scale stochastic dynamical systems are ubiquitous in science and engineering, and the reduction of such systems and their models to only their slow components is often essential for scientific computation and further analysis. Rather than being available in the form of an explicit analytical model, often such systems can only be observed as a data set which exhibits dynamics on several time scales. We will focus on applying and adapting data mining and manifold learning techniques to detect the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 48 publications
0
49
0
Order By: Relevance
“…Several studies, e.g. [21], [33] and [34], have shown that based on properties of the diffusion maps coordinates, this assumption commonly holds. Third, we specified the conditions under which the Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, e.g. [21], [33] and [34], have shown that based on properties of the diffusion maps coordinates, this assumption commonly holds. Third, we specified the conditions under which the Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This approximation has been used is several papers [18,17,16,19,27,37,40,38,39,41] and error analysis for it was presented in [17,37]. The approximation can be viewed as a result of the relation between the intrinsic and observed manifolds.…”
Section: 1mentioning
confidence: 99%
“…The locality of the approximation is demonstrated empirically in section 6. In addition, rigorous error analysis was provided in [17], where it was shown that the approximation is accurate for points on the observed manifold when y i − y j 4 is sufficiently small with respect to the higher derivatives of the observation function.…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation
“…However, as pointed out by Lafon 21, anisotropic diffusion maps can be computed by using different norms. This issue has been extensively studied recently, and several norms and metrics have been developed for this purpose (22)(23)(24).…”
Section: Geometry Learning Of Dynamics From Observationsmentioning
confidence: 99%